Etiology and Clinical Characterization of Respiratory Virus Infections in Adult Patients Attending an Emergency Department in Beijing - Yu, Xiaoyan; Lu, Roujian; Wang, Zhong; Zhu, Na; Wang, Wen; Julian, Druce; Chris, Birch; Lv, Jianxin; Tan, Wenjie (PLOS ONE, 2012)
Background Acute respiratory tract infections (ARTIs) represent a serious global health burden. To date, few reports have addressed the prevalence of respiratory viruses (RVs) in adults with ARTIs attending an emergency department (ED). Therefore, the potential impact of respiratory virus infections on such patients remains unknown. Methodology/Principal Findings To determine the epidemiological and clinical profiles of common and recently discovered respiratory viruses in adults with ARTIs attending an ED in Beijing, a 1-year consecutive study was conducted from May, 2010, to April, 2011. Nose and throat swab samples from 416 ARTI patients were checked for 13 respiratory viruses using multiple reverse transcription polymerase chain reaction(RT-PCR) assays for common respiratory viruses, including influenza viruses (Flu) A, B, and adenoviruses (ADVs), picornaviruses (PICs), respiratory syncytial virus (RSV), parainfluenza viruses (PIVs) 1–3, combined with real-time RT-PCR for human metapneumovirus (HMPV) and human coronaviruses (HCoVs, -OC43, -229E, -NL63, and -HKU1). Viral pathogens were detected in 52.88% (220/416) of patient samples, and 7.21% (30/416) of patients tested positive for more than one virus. PICs (17.79%) were the dominant agents detected, followed by FluA (16.11%), HCoVs (11.78%), and ADV (11.30%). HMPV, PIVs, and FluB were also detected (<3%), but not RSV. The total prevalence and the dominant virus infections detected differed significantly between ours and a previous report. Co-infection rates were high for HCoV-229E (12/39, 30.76%), PIC (22/74, 29.73%), ADV (12/47, 25.53%) and FluA (15/67, 22.39%). Different patterns of clinical symptoms were associated with different respiratory viruses. Conclusions The pattern of RV involvement in adults with ARTIs attending an ED in China differs from that previously reported. The high prevalence of viruses (PIC, FluA, HCoVs and ADV) reported here strongly highlight the need for the development of safe and effective therapeutic approaches for these viruses.